Notes on Early Land Plants Today. 53. Hygrobiellaceae (Marchantiophyta) validated - Konstantinova, Nadezda A.; Vilnet, Anna A.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
When describing the family Hygrobiellaceae, Konstantinova & Vilnet (2010) did not cite the basionym, but a combination of the taxon, thus not fulfilling the requirement in ICN Art. 41.5 (McNeill et al. 2012) of a full and direct citation of the basionym. This is corrected here.